Developmental trajectories of EEG sleep slow wave activity as a marker for motor skill development during adolescence: a pilot study. Issue 1 (12th July 2016) - Lustenberger, Caroline; Mouthon, Anne‐Laure; Tesler, Noemi; Kurth, Salome; Ringli, Maya; Buchmann, Andreas; Jenni, Oskar G.; Huber, Reto
Abstract: Reliable markers for brain maturation are important to identify neural deviations that eventually predict the development of mental illnesses. Recent studies have proposed topographical EEG‐derived slow wave activity (SWA) during NREM sleep as a mirror of cortical development. However, studies about the longitudinal stability as well as the relationship with behavioral skills are needed before SWA topography may be considered such a reliable marker. We examined six subjects longitudinally (over 5.1 years) using high‐density EEG and a visuomotor learning task. All subjects showed a steady increase of SWA at a frontal electrode and a decrease in central electrodes. Despite these large changes in EEG power, SWA topography was relatively stable within each subject during development indicating individual trait‐like characteristics. Moreover, the SWA changes in the central cluster were related to the development of specific visuomotor skills. Taken together with the previous work in this domain, our results suggest that EEG sleep SWA represents a marker for motor skill development and further supports the idea that SWA mirrors cortical development during childhood and adolescence.